2019
DOI: 10.3389/fphar.2019.00334
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Ajuga Species Extracts Modulate Supportive Processes for Cancer Cell Development

Abstract: Backround: Ajuga species have been used in traditional medicine for their diuretic, anti-inflammatory, wound-healing, and hepatoprotective properties. Purpose: The phytochemical profile and anticancer potential of three Ajuga sp. ( A. genevensis, A. chamaepitys , and A. laxmannii ) from Romania was investigated. Materials and Methods: The phytochemicals were extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…The genus Ajuga (Lamiaceae) encompasses more than 300 annual and perennial species across the globe [ 1 , 2 ]. The traditional use of several of these species to address diabetes, fever, rheumatism, tuberculosis, and high blood pressure on account of the presence of many bioactive compounds with anti-inflammatory, antioxidant, antibacterial, or anti-tumor activities is known [ 3 , 4 , 5 , 6 ]. The use of some Ajuga species as ornamentals, given their distinctive leaves, bracts, or flowers, is also prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Ajuga (Lamiaceae) encompasses more than 300 annual and perennial species across the globe [ 1 , 2 ]. The traditional use of several of these species to address diabetes, fever, rheumatism, tuberculosis, and high blood pressure on account of the presence of many bioactive compounds with anti-inflammatory, antioxidant, antibacterial, or anti-tumor activities is known [ 3 , 4 , 5 , 6 ]. The use of some Ajuga species as ornamentals, given their distinctive leaves, bracts, or flowers, is also prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of a combination therapy with flavonoids is already being researched. Firstly, numerous studies confirmed that flavonoids show better anti-tumor activity when used in complex preparations containing a mixture of several compounds from this group [25][26][27][28][29][30][31]. Such reports mainly focused on the health-promoting role of food rich in flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical constituents of Ajuga genus are varied including diterpenoids, [1–11] iridoids, [12–14] steroids, [15–17] glycosides, [18,19] and flavonoids [20] . Some of them showed anti‐inflammatory, [21–23] antibacterial, [24] antidiabetic, [25,26] antimutagenic, [27] immunoregulatory effects, [28] antiviral, [29] antiplasmodial, [30,31] and antitumor activities [32,33] . Ajuga nipponensis Makino is widely distributed in east, central south, and southwest of China [34] .…”
Section: Introductionmentioning
confidence: 99%
“…[20] Some of them showed antiinflammatory, [21][22][23] antibacterial, [24] antidiabetic, [25,26] antimutagenic, [27] immunoregulatory effects, [28] antiviral, [29] antiplasmodial, [30,31] and antitumor activities. [32,33] Ajuga nipponensis Makino is widely distributed in east, central south, and southwest of China. [34] It has been traditionally used to treat several diseases such as sore throat, phlegm, and fever.…”
Section: Introductionmentioning
confidence: 99%